Konsep Penciptaan dan Reproduksi Manusia: Integrasi Islam dan Sains Serta Implikasinya dalam Pendidikan Agama Islam - herlini; Risnawati; Muharrani (Al-Mutharahah: Jurnal Penelitian dan Kajian Sosial Keagamaan, 2024)
Abstract This research discusses the concept of human creation and reproduction in Islam, as well as the integration between religious teachings and science, particularly science, with a focus on its implications in Islamic religious education. The purpose of this research is to analyze the Islamic understanding of human creation and reproduction and how modern scientific knowledge, such as embryology, can contribute to enriching this understanding in an educational context. The research method used is a literature review by analyzing Islamic theological sources, current scientific literature on reproduction and embryology, and a study of the Islamic religious education curriculum. The results show that the understanding of human creation in Islam can be integrated with scientific knowledge in order to strengthen religious education. This integration not only improves students' understanding of both fields, but also demonstrates the harmony between religious teachings and science. The conclusion of this study is that collaboration between the Islamic concept of human creation and scientific knowledge has the potential to improve the quality of Islamic religious education, as well as foster a critical and open attitude among students towards the relationship between faith and science. Keywords: human creation; human reproduction; Islamic religious education; integration of Islam and science Abstrak Penelitian ini membahas konsep penciptaan dan reproduksi manusia dalam Islam, serta integrasi antara ajaran agama dan ilmu pengetahuan, khususnya sains, dengan fokus pada implikasinya dalam pendidikan agama Islam. Tujuan penelitian ini adalah untuk menganalisis pemahaman Islam tentang penciptaan manusia dan proses reproduksi, serta bagaimana pengetahuan ilmiah modern, seperti embriologi, dapat berkontribusi dalam memperkaya pemahaman tersebut dalam konteks pendidikan. Metode penelitian yang digunakan adalah kajian literatur dengan menganalisis sumber-sumber teologi Islam, literatur ilmiah terkini mengenai reproduksi dan embriologi, serta studi tentang kurikulum pendidikan agama Islam. Hasil penelitian menunjukkan bahwa pemahaman tentang penciptaan manusia dalam Islam dapat diintegrasikan dengan pengetahuan ilmiah dalam rangka memperkuat pendidikan agama. Integrasi ini tidak hanya meningkatkan pemahaman siswa terhadap kedua bidang tersebut, tetapi juga memperlihatkan keselarasan antara ajaran agama dan ilmu pengetahuan. Simpulan dari penelitian ini adalah bahwa kolaborasi antara konsep Islam tentang penciptaan manusia dan pengetahuan sains berpotensi meningkatkan kualitas pendidikan agama Islam, serta menumbuhkan sikap kritis dan terbuka di kalangan peserta didik terhadap hubungan antara iman dan ilmu. Kata Kunci: penciptaan manusia; reproduksi manusia; pendidikan agama Islam; integrasi Islam dan sains.